2017
DOI: 10.1021/acsami.6b14051
|View full text |Cite
|
Sign up to set email alerts
|

2-Fold Interpenetrating Bifunctional Cd-Metal–Organic Frameworks: Highly Selective Adsorption for CO2 and Sensitive Luminescent Sensing of Nitro Aromatic 2,4,6-Trinitrophenol

Abstract: A robust primitive diamond-type topology 3-D metal-organic framework (MOF) of {[Cd(hbhdpy)(bdc)(DMA)]·(HO)} (1, DMA = N,N-dimethylacetamide) was constructed from the planar secondary building units of the dinuclear cadmium clusters, Cd(μ-O), and two linear organic linkers of the new multidentate Schiff base of 4-(2-hydroxy-3-methoxy-benzyli-denehydrazino-carbonyl)-N-pyridin-4-yl-benzamide (Hhbhdpy) through the solvothermal reaction. 1 presents a 2-fold interpenetrating network along with confined narrow channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(43 citation statements)
references
References 41 publications
0
43
0
Order By: Relevance
“…The PXRD pattern of compound 1a remained stable after the adsorption of N 2 and CO 2 (Supplementary Figure S11). Considering the adsorption isotherm at 298 K, the observed CO 2 adsorption capacity of 1a is better than the metal-organic frameworks including [Zn(BPTC) 0.5 (Tz) (Hong et al, 2017;Kong et al, 2018;Yao et al, 2018;Zhou et al, 2018;Liu et al, 2019). The adsorption isotherms show typical type-I sorption isotherm with fast kinetics and good reversibility, further indicating its microporosity.…”
Section: Gas Sorption Experimentsmentioning
confidence: 90%
“…The PXRD pattern of compound 1a remained stable after the adsorption of N 2 and CO 2 (Supplementary Figure S11). Considering the adsorption isotherm at 298 K, the observed CO 2 adsorption capacity of 1a is better than the metal-organic frameworks including [Zn(BPTC) 0.5 (Tz) (Hong et al, 2017;Kong et al, 2018;Yao et al, 2018;Zhou et al, 2018;Liu et al, 2019). The adsorption isotherms show typical type-I sorption isotherm with fast kinetics and good reversibility, further indicating its microporosity.…”
Section: Gas Sorption Experimentsmentioning
confidence: 90%
“…Our previous research indicated that the presence of π•••π conjugation between benzimidazoles in complexes can cause partial fluorescence quenching. [39][40][41] In this work, this is the first time that we have found that the π•••π conjugation leads to complete quenching of fluorescence, 42,43 which may be related to picric acid that is often used as a fluorescence quenching reagent. The observations provide evidence for the fluorescence quenching mechanism of picrate.…”
Section: Fluorescent Propertiesmentioning
confidence: 99%
“…Due to the great luminescent performances of the Hmdpt linker and d 10 complexes (Chou et al, 2014;Kumar et al, 2014;Hu et al, 2015;Ye et al, 2015;Wang et al, 2016;Hong et al, 2017;Lim et al, 2017), the solid-state photoluminescence properties have been studied for the four complexes and Hmdpt as well as the various auxiliary benzendicarboxylates at room temperature (Figure 11 and Supplementary Figure 13), the emissions of which are given in Supplementary Table 2. The free Hmdpt shows the band at 472 nm when excited at 307 nm, attributing to the π * → π transition of the intra-ligand (Lin et al, 2017).…”
Section: Luminescent Propertiesmentioning
confidence: 99%
“…The coordination polymers (CPs) have gained considerable research interest by the self-assembly of various organic linkers (including different functional groups) with metal ions/clusters due to their special topological nets and broad applications (Wang et al, 2014Smith et al, 2015;Dey et al, 2017;Hong et al, 2017;Islamoglu et al, 2017;Kariem et al, 2017;Lin et al, 2017;Li et al, 2018;Xing and Janiak, 2020;Zhang et al, 2020). Generally, the coordination preference of the nature of ligands and geometries of ions are the primary considerations in the preparation process of CPs.…”
Section: Introductionmentioning
confidence: 99%